2021
DOI: 10.1186/s13287-020-02083-x
|View full text |Cite
|
Sign up to set email alerts
|

microRNA-186 in extracellular vesicles from bone marrow mesenchymal stem cells alleviates idiopathic pulmonary fibrosis via interaction with SOX4 and DKK1

Abstract: Background Previous reports have identified that human bone marrow mesenchymal stem cell-derived extracellular vesicles (BMSC-EVs) with their cargo microRNAs (miRNAs) are a promising therapeutic approach for the treatment of idiopathic pulmonary fibrosis (IPF). Therefore, we explored whether delivery of microRNA-186 (miR-186), a downregulated miRNA in IPF, by BMSC EVs could interfere with the progression of IPF in a murine model. Methods In a co-cu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
33
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 39 publications
(34 citation statements)
references
References 39 publications
1
33
0
Order By: Relevance
“…Numerous countries around the world have carried out phase I clinical trials on MSCs for the treatment of IPF to evaluate the safety of stem cell therapy [ 26 , 27 ]. EVs derived from MSCs are considered as a potential method for the treatment of fibrotic diseases[ 15 , 28 ]. Therefore, we extracted EVs from IMRCs to further evaluate their tissue repair and anti-inflammatory, anti-fibrosis and immune regulation effects.…”
Section: Discussionmentioning
confidence: 99%
“…Numerous countries around the world have carried out phase I clinical trials on MSCs for the treatment of IPF to evaluate the safety of stem cell therapy [ 26 , 27 ]. EVs derived from MSCs are considered as a potential method for the treatment of fibrotic diseases[ 15 , 28 ]. Therefore, we extracted EVs from IMRCs to further evaluate their tissue repair and anti-inflammatory, anti-fibrosis and immune regulation effects.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, numerous preclinical studies have demonstrated the antifibrotic effect of MSC-EVs in the lung (139), liver (140), kidney (141), and heart (142). Focusing on liver fibrosis, MSC-EVs promote liver tissue repair by reducing inflammation, therefore alleviating fibrosis.…”
Section: Liver Fibrosismentioning
confidence: 99%
“…Three studies indicated MSC-EVs inhibited pulmonary fibrosis by transferring microRNAs. Zhou et al (Zhou et al, 2021) found that EVs from human BM-MSCs blocked fibroblast activation and suppressed SOX4, DKK1 expression by transferring miR-186. Human BM-MSCs derived EVs could also suppress the fibroblast proliferation by downregulating FZD6 expression via carrying miR-29b-3p (Wan et al, 2020).…”
Section: Pulmonary Fibrosismentioning
confidence: 99%